Improving The Quality of Learning Through The Use of The Canva Application in Mathematics Learning Class VI SD Negeri 2 Krakal - Ariyanti, Puri; Saryanto, Saryanto; Rejokirono, Rejokirono (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This writing aims to find out the Improvement of Learning Quality Through the Canva Application in Mathematics Learning Class VI SD Negeri 2 Krakal. The problems that are the focus of the study in this writing are; Is it through learning media that the Canva application can improve the quality of learning and Is it through the media that the student canva application is easier to defend. The research method used is a qualitative research method with a literature review approach , namely by conducting a literature review, the use of the Canva application and problems in mathematics learning. Based on the author’s results, it can be concluded that the existence of learning by utilizing information technology through the use of the Canva application as a learning medium is proven to improve the quality of learning, Learning by utilizing information technology through the use of the Canva application as a learning medium is proven to make it easier to understand the material, Learning by utilizing information technology through the use of the Canva application as a learning medium Learning media has been proven to improve student learning outcomes, and There is a positive correlation between the quality of learning and student learning outcomes, the better the quality of learning, the higher the interest in learning and the success of students in learning.